MODERN LABORATORY DIAGNOSTICS OF THYROID DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Thyroid diseases are among the most prevalent endocrine disorders globally, affecting millions of individuals across all age groups. Accurate and timely diagnosis is critical for effective management and treatment. Advances in laboratory diagnostics have revolutionized the ability to detect, monitor, and manage thyroid dysfunctions, ensuring better patient outcomes. This article explores the modern approaches to laboratory diagnostics of thyroid diseases.